Kingdom of the Netherlands-Netherlands Antilles : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2003)
This Selected Issues paper and Statistical Appendix for Netherlands Antilles examines the economic growth in Small Island Economies. The paper finds that the Small Island Economies as a group grew faster than the rest of the world during 1960-85. The paper analyzes whether Small Island Economies respond to the same set of growth determinants as other economies, and concludes that growth is determined by the same factors and macroeconomic policy choices. The paper presents possible economic challenges that Small Island Economies might face owing to their size.